Library Automation Systems Integration (Case: ELIB and SLiMS) - Muhammad, Meizano Ardhi; Mardiana, Mardiana (International Series on Interdisciplinary Science and Technology, 2016)
Abstract—The Library automation system help reduce much work need to be done by doing monotonous routine jobs with the help of technologies such as Barcode and RFID. Unila Library as the pioneer of RFID technology implementation in Lampung province face challenge in migration. Unila Library used SLiMS Library Automation System to manage collections, which use mainly barcode to identify collection. RFID uses allow collections to be scanned in gate and warn librarian. Unfortunately, SLiMS doesn’t support SIP2 protocol which is needed by RFID devices (gate, kiosk) to function properly. Therefore, a solution must be made to address the migration of data and support SIP2 protocol. ELIB is a library automation software which support SIP2 protocol. So, library automation systems integration which synchronize both database in ELIB and SLiMS to keep up to date data and allow support for SIP2 protocol must be made in the form of middleware. Some of difficulties arise in integration was the development of both library automation systems which require fine tuning everytime update occurs and both systems in active use. Benchmarking is done to find anomaly and disreparancies of data. And, because the integration system is build as middleware, it remain flexible and open to future development. It can be concluded, Library automation systems integration require vigilance and keen observations into minuscule level especially because both systems are so different. Keywords— library, RFID, ELIB, SLIMS, SIP2, middleware